Event-triggered estimation and model predictive control for linear systems with actuator fault - Lu, Qing; Shi, Peng; Wu, Ligang; Lim, Cheng-Chew (IET control theory & applications, 2020)
This study is concerned with the design of an event-triggered fault estimation and fault tolerant model predictive control scheme for linear systems subject to disturbances and actuator faults by using the method of delta operator. First, an observer is established to estimate the state and the fault simultaneously. An $H_{2}/H_{∞ }$H2/H∞ model predictive controller with fault compensation signals is then proposed through solving a constrained optimisation problem. An event-triggered scheme is employed to conserve the network bandwidth. The new design techniques are shown to be effective via simulation results.